Meningkatkan Ekonomi Kreatif Masyarakat Banjar Petang Suci Melalui Optimalisasi Peran Media Sosial Dalam Meningkatkan Penjualan Produk Industri Rumahan - Gusti Ayu Made Suarniti (Universitas Warmadewa, 2021)
The Banjar Petang Suci area is a densely populated area, most of the people fulfill their daily needs through home industries. Income from the industrial sector in the Banjar Petang Suci area can be increased by introducing creative economy programs and procedures for using social media presented by KKN (Real Work Class) students. The purpose of this activity is to improve the economy of the residents of Banjar Petang Suci and increase the social competence of students who participate in KKN activities. The method used to achieve this goal is through educational programs through counseling to villagers about the role of social media in increasing the marketability of home industry products. The program is carried out in conjunction with other activities that are able to develop the Banjar Petang Suci community in other sectors, such as teaching activities and holding sanitation activities at SDN 1 Petang, Posyandu activities at the Banjar Petang Suci hall, participating in gotong royong activities with residents and youth of Banjar Petang Suci, participating in elderly gymnastics activities, mapping the boundaries of the Banjar Petang Suci area, participating in activities to commemorate August 17, and mentoring for 2 families in Banjar Petang Suci. It can be concluded that this KKN activity ran smoothly. Students gain knowledge and experience, the people of Banjar Petang Suci get information about social media needed to develop creative economic activities, namely increasing sales of home industry products. Mahasiswa memperoleh ilmu dan pengalaman, masyarakat Banjar Petang Suci mendapatkan informasi mengenai media sosial yang diperlukan guna mengembangkan kegiatan ekonomi kreatif yaitu meningkatkan penjualan produk industri rumahan.